Diagnosis of atypia/follicular lesion of undetermined significance: An institutional experience - Wong, Lawrence Q. (Medknow Publications & Media Pvt Ltd, 2014)
BACKGROUND: The overall malignancy rate for the thyroid fine-needle aspiration (FNA) diagnosed as atypia of undetermined significance/follicular lesion of undetermined significance (AUS/FLUS) ranges from 5% to 30%. In this study, we present our institutional experience with thyroid nodules diagnosed as AUS/FLUS and further stratified into subcategories. In addition, we also assessed the significance of various clinicopathologic factors that may influence AUS/FLUS diagnoses and their outcomes. DESIGN: A search of our laboratory information system was performed to identify all in-house thyroid FNA cases diagnosed as AUS/FLUS from 2008 to 2012. The data were collected and characterized by patient demographic information, cytopathology diagnosis with sub-classifiers and follow-up. RESULTS: The case cohort included 457 cases diagnosed as AUS/FLUS. These were further sub-classified into one of six subcategories depending on the cytomorphologic findings and suspicion for or against a neoplastic process. Of the 457 cases, repeat FNA and/or surgical follow-up was available in 363 cases. There were 182 (39.8%) cases with cytologic follow-up only; 18 (9.9%) remained as AUS/FLUS, while 158 (86.8%) were re-classified with the majority being benign (142 cases). Histologic follow-up was available in 181 (39.6%) cases. There were 60 malignant cases confirmed by surgical excision, with an overall malignancy rate of 33.1%. The malignancy rate was 38.8% for cases with a repeat FNA versus 25.6% for cases that went directly to surgery without a repeat FNA. Papillary thyroid carcinoma accounted for 93.3% (56 cases) of the malignant cases. CONCLUSION: Based on our study, even though the malignancy rate of AUS/FLUS cases is similar to those reported for cases diagnosed as follicular neoplasm/suspicious for follicular neoplasm, we are of the belief that these comparable malignancy rates are a product of better clinical management and selection of patients diagnosed as AUS/FLUS for surgery after a repeat FNA.